Optimization of Literated Culture Through the Utilization of the Reading Area at SDN 3 Mojorebo, Wirosari District, Grobogan Regency - Nurmalasari, Merliana Dyah; Wakhyudin, Husni; Rahmawati, Intan (Journal of Education Research and Evaluation, 2019)
This study aims to describe 1) the efforts of the school to introduce a culture of reading 2) optimize the reading culture 3) obstacles in optimizing the use of the reading corner area 4) solutions to obstacles in optimizing the reading culture. The type of research used is qualitative research. The informants in this study were principals, teachers and children who had problems learning to read. Research results show that: 1) Efforts from the school to foster students' reading culture are conveyed by the principal by inviting publishers to provide choices of books to be given to students. 2) the benefits of reading corners provide a new atmosphere in the classroom, also when there is free time can be used to read. In addition, making students enjoy reading by being guided by the teacher. 3) Obstacles in optimizing literacy culture, namely the difficulty of fostering a reading culture early on. 4) Solutions in optimizing the culture of literacy, among others, the teacher provides reading books that are appropriate to the needs of students and try to add a collection of reading so that students do not get tired of reading in the reading corner